2019
DOI: 10.1002/jcp.28343
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance and prognostic value of Xenopus kinesin‐like protein 2 expressions in human tumors: A systematic review and meta‐analysis

Abstract: Targeting protein for Xenopus kinesin‐like protein 2 (TPX2) is a microtubule‐associated protein that plays a pivotal part in the formation of spindles. There is accumulating evidence that the expression of TPX2 is upregulated in many kinds of human cancers and that this protein is involved in the occurrence and progression of tumors. The purpose of this meta‐analysis was to investigate the relationship between the overexpression of TPX2 and poor prognosis in cancer patients. A total of 18 eligible studies enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…TPX2, locates at 20q11.21, is one of the main spindle assembly factors that play a key role in inducing microtubule assembly and growth during M phase of mitosis [4951]. Previous studies reported that TPX2 mRNA expression during cell cycle progression is high in G2/M phase, decreases dramatically upon G1 phase entry, increases upon entry into S phase, and peaks again at the next G2/M phase [5256].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TPX2, locates at 20q11.21, is one of the main spindle assembly factors that play a key role in inducing microtubule assembly and growth during M phase of mitosis [4951]. Previous studies reported that TPX2 mRNA expression during cell cycle progression is high in G2/M phase, decreases dramatically upon G1 phase entry, increases upon entry into S phase, and peaks again at the next G2/M phase [5256].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its important role in microtubule assembly and mitosis, TPX2 has been found to be over expressed in various human cancers, for instance clear renal cell carcinoma [58], esophageal carcinoma [59], hepatocellular carcinoma (HCC) [52, 60], gastric cancer [61], bladder carcinoma [62] and so on. TPX2 expression has been shown to be positively correlated with poor prognosis, metastasis, and recurrence [49, 63].…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of TPX2 induces the amplification of centrosomes and leads to DNA polyploidy 32 . Increasing evidences show that upregulated TPX2 expression is associated with more aggressive cancer cells, promoting cancer development and metastasis 33 . Elevated expression of CKS1B has been associated with cell proliferation and poor prognosis in numerous tumor types, including oral, gastric, breast and colon carcinoma 34 .…”
Section: Discussionmentioning
confidence: 99%
“…TPX2 gene encodes a microtubule-associated protein, which serves a vital role in mitotic spindle formation and chromosome segregation process [24,25]. The overexpression of TPX2 has been reported in many studies and related to poor clinical outcomes of multiple malignancies, such as lung cancer, thyroid carcinoma, clear cell renal carcinoma, gastrointestinal cancer, and hepatocellular cancer, implying the possibility that TPX2 can be used as a prognostic marker and potential therapeutic target in these tumors [26][27][28][29][30][31][32][33][34]. Furthermore, TPX2 was reported to be involved in the invasion of tumor cells by the elevation of MMP2 and MMP9 through AKT signaling in hepatocellular carcinoma [35,36].…”
Section: Discussionmentioning
confidence: 99%